Pengaruh Financial Literacy, Financial Behavior, Financial Attitude, Dan Demografi Terhadap Perilaku Konsumtif ( Studi Pada Mahasiswa Strata I Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya ) - Prihastuty, Dyah Rini; Rahayuningsih, Sri (JHP17 (Jurnal Hasil Penelitian), 2018)
This study aims to determine the effect of financial literacy, financial behavior,financial attitude, and demography on consumptive behavior. This study used questionnaireswith a sample of 100 students of the Faculty of Economics, University of 17 Agustus 1945Surabaya using. The sampling technique used purposive sampling technique. Data analysis inthis research use SEM (Structural Equation Modeling) with application of PLS program(Partial Least Square).The results of this study indicate that financial literacy significantlynegatively affect consumptive behavior, financial behavior has a positive effect significantlyon consumptive behavior, financial attitude has a positive effect on consumptive behavior,and demography has a positive effect on consumptive behavior on the students of the Facultyof Economics, University of 17 Agustus 1945 Surabaya.Keywords: Financial Literacy, Financial Behavior, Financial Attitude, Demography,ConsumptiveBehavior